Resolve in International Politics - Kertzer, Joshua D., 1984- (Book collections on Project MUSE., 2016)
"Why do some leaders and segments of the public display remarkable persistence in confrontations in international politics, while others cut and run? The answer given by policymakers, pundits, and political scientists usually relates to issues of resolve. Yet, though we rely on resolve to explain almost every phenomenon in international politics--from prevailing at the bargaining table to winning on the battlefield--we don't understand what it is, how it works, or where it comes from. Resolve in International Politics draws on a growing body of research in psychology and behavioral economics to explore the foundations of this important idea. Joshua Kertzer argues that political will is more than just a metaphor or figure of speech: the same traits social scientists and decision-making scholars use to comprehend willpower in our daily lives also shape how we respond to the costs of war and conflict. Combining laboratory and survey experiments with studies of great power military interventions in the postwar era from 1946 to 2003, Kertzer shows how time and risk preferences, honor orientation, and self-control help explain the ways leaders and members of the public define the situations they face and weigh the trade-offs between the costs of fighting and the costs of backing down. Offering a novel in-depth look at how willpower functions in international relations, Resolve in International Politics has critical implications for understanding political psychology, public opinion about foreign policy, leaders in military interventions, and international security."--